KREATIVITAS ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA BAGAN SINEMBAH - FATMAWAHYUNI, Tengku; Indarto, Wusono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak: Creativity is the ability that reflects smoothness, suppleness, and builder and the ability collaborate an idea. Based on the observations of researchers a child's creativity symptoms is low, 1) the child is lacking in conducting free drawing of the basic forms of basic points, triangles, and rectangles. 2) the child is less able to carry out the activities of the free drawing using colored pencil media. 3) the existence of children who are less able to make his own work. Instrument data collection in the form of sheets observation of the child. Analysis techniques using a percentage formula. From the research results obtained by the creativity of children of 10 aspects the highest percentage in the tenth aspect, namely 75.43%, based on the assessment categories can be categorized as "Good". While the lowest aspect of the aspects to one that is 54.38% can be categorized as "Enough", while the second aspect is 62.28% can be categorized enough third aspect 69.29 can be considered "good" fourth aspect of 67.54% can be categorized as "Good", The fifth aspect of 64.91% can be categorized as "Good", the sixth aspect of 72.80% can be categorized as "Good" seventh aspect 61.40% can be categorized as "Enough", 70.17% the eighth aspect can be categorized as "Good", aspects kesembilan74.56% can be categorized as "Good". So the results of the calculation of all aspects of it can be concluded that the creativity of children aged 5-6 years in kindergarten Chart Pembina State Sinembah in the category "Good" with a percentage of 67.27%.Keywords : Creativity of Children, Ages 5-6 Years